The Influence Of Using Peer Assisted Learning Strategies (Pals) Towards Students Achievement In Reading Comprehension At The SMPN 7 Pematangsiantar - Semaria Eva Elita Girsang; Indra Jayanti Damanik; Roslina Sihotang (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The objective of this study is to identify the significantly effect on the students’ achievement in reading comprehension by Peer Assisted Learning Strategy (PALS). This research is an experimental which was conducted at SMPN 7 Pematangsiatar. Academic year 2022/2023. The population of this research was the second grade which distributed into two classes with total 64 students. Experimental class consisted of 32 students and control class consisted 32 students. The instruments for collecting data in this research was written test in form multiple choice test, consist of 20 questions. Pre-test and post-test were conducted in both, experimental and control group. The data of post-test was analyzed by using SPSS Version 22.00. The result of the research shows that the testing hypothesis of post-test scores was found that that tcount (0.970) >ttable (2.188) at the significance level α =0.05 with the degrees of freedom (df) = 31, and 0,340 for the sig (2-tailed). Ho (Peer Assisted Learning Strategy doesn’t influence to students reading comprehension) is rejected and Ha (Peer Assisted Learning Strategy influence to students in reading comprehension) is accepted. It means that there are the Influence Of Using Peer Assisted Learning Strategies (PALS) Towards Students Achievement In Reading Comprehension in Narrative Text at SMP Negeri 7 Pematangsiantar